Exploring an EFL teacher’s experiences in using Canva for Teaching English Vocabulary: Non-English Education Teacher's Perspective - Priska Delfiana; Desy Rusmawaty; Ventje Kalukar (Institute of Computer Science (IOCS), 2023)
This study is a single case study that tries to examine the experiences of an English Foreign Language (EFL) teacher in employing Canva, a graphic design platform, as an instructional tool for vocabulary teaching and to investigate the experiences, benefits, challenges, and familiarity of integrating Canva into educational settings. The process of data collection encompassed qualitative methodology, specifically interviews and document analysis, which is the output of using Canva and is conducted by the participant, who is a teacher who has been actively involved in the use of Canva since 2015 and with a unique background of education, which is the Faculty of Social and Political Sciences. Notwithstanding, she enrolled in the Faculty of Teaching and Education, specifically in English Education. This study uses constructivism as the theoretical framework to explore her background, experiences, and familiarity in a Narrative Single Case study. The findings revealed that EFL vocabulary teaching strategies and the potential of Canva to enhance education. Canva provides a personalized visual constructivism platform, promoting vocabulary comprehension and retention. Canva also facilitates assessment strategies, which encourages student participation. Canva holds promise for the future of EFL vocabulary instruction and study. Further research is recommended to determine the long-term effects on learners' vocabulary acquisition and to explore potential strategies for overcoming the identified challenges. (9 pt).